Factors associated with cardiovascular disease in the Brazilian adult population: National Health Survey, 2019 - Crizian Saar Gomes; Renata Patrícia Fonseca Gonçalves; Alanna Gomes da Silva; Ana Carolina Micheletti Gomide Nogueira de Sá; Francielle Thalita Almeida Alves; Antonio Luiz Pinho Ribeiro; Deborah Carvalho Malta
ABSTRACT Objective: to estimate the prevalence and investigate the sociodemographic, health, and lifestyle factors associated with the self-reported diagnosis of Cardiovascular Disease (CVD) in the adult Brazilian population. Methods: Data from the National Health Survey (PNS 2019) were analyzed. The presence of CVD was self-reported through the question: "Has any doctor ever given you a diagnosis of heart disease?". Sociodemographic factors, health conditions, and lifestyle were evaluated. For data analysis, Poisson Regression with robust variance was used. Results: 5.3% (95%CI 5.04-5.57) of Brazilian adults reported CVD, of which, 29.08% (95%CI 27.04-31.21) underwent coronary artery bypass surgery or angioplasty and 8.26% (95%CI 7.09-9.6) reported severe limitation in usual activities due to CVD. The factors associated with CVD were advanced age; being male; white race/color; complete middle school and incomplete high school education; have health insurance; self-assessing health as regular or bad/very bad; self-reported hypertension, high cholesterol, and diabetes; being a former smoker; consuming fruits and vegetables as recommended; not consuming alcohol in excess; and not practicing leisure-time physical activity. Conclusions: CVD is associated with sociodemographic, health, and lifestyle factors. It is important to support public policies, programs, and goals for the reduction of cardiovascular diseases in Brazil, especially in the most vulnerable groups.